Unmanned air vehicle flights within airspace - Stankunas, J.; Ziliene, D. (Proceedings of National Aviation University (archive), 2003)
Recent years have shown a rapid increase in air traffic. Unmanned Air Vehicles will deteriorate this situation. For this reason, Air Traffic Management should be adopt Unmanned Air Vehicles, than Unmanned Air Vehicles flights within Controlled Airspace, Uncontrolled Airspace and Special Use Airspace